PERLINDUNGAN DAN PENGALIHAN ATAS HAK ATAS KEKAYAAN INTELEKTUAL (Hak cipta) - Takdir Takdir (MUAMALAH, 2015)
Intellectual Property is very important for the creator's own interests, for it will be discussed in this paper about how the protection of Copyright and the transfer of the copyright. Method used in this paper is a qualitative method of collecting the data source library (Library Research). Under Article 12 of the Copyright Act that protected creation is creation in the fields of science, art, and literary works which include: books, computer programs, pamphlets, typographical arrangement arrangement (Lay Out), published works, and all the work write; Lectures, lectures, speeches, and other similar creatures with it; Props made for the purposes of education and science; Copyrighted songs or music with or without text; Drama, musical dramas, dance, choreography, puppetry, and pantomin; Fine art in all forms such as painting, drawing, sculpture, calligraphy, sculpture, sculpture, collage and art terapa; Architecture; map; Batik art; Photos pornography; Sinemato pornography; Translations, interpretations, adaptations, anthologies, databases, and other works from the transferor embodiment. In Article 3 of the Copyright Act, copyright may be transferred in whole or as passing: Inheritance; grant; probate; Agreement is limited. Other causes prescribed by Regulations This transfer of copyright must be in writing either by deed or without deed notary, so that this transfer should be based on an agreement